Implementasi Kebijakan Dispensasi Nikah Berdasarkan UU No. 16 Tahun 2019 di Kecamatan Dukuh Pakis Kota Surabaya - Safitri, Diana (IAI Nasional Laa Roiba Bogor, 2024)
This study aims to determine the implementation of the marriage dispensation policy based on Law No. 16 of 2019 in Dukuh Pakis District, Surabaya City. This research method is a descriptive qualitative research method. This research analysis uses Implementation Theory according to Daniel A. Mazmanian and Paul A. Sabatier including problem characteristics, policy or law characteristics and environmental variables. The results showed that the implementation of marriage dispensation in Dukuh Pakis District was still less than optimal, the granting of this marriage dispensation occurred due to the urgent situation of the prospective bride and groom so that the marriage had to be carried out immediately even though the age of the prospective bride and groom was under 19 years old. This problem occurs due to pregnancy outside of marriage so that a marriage dispensation must be given in accordance with Law No. 16 of 2019 so that the prospective bride and groom can immediately get married.